2003
DOI: 10.1007/s00439-002-0892-2
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic disease caused by de novo mitochondrial-nuclear DNA transfer

Abstract: Transfer of nucleic acid from cytoplasmic organelles to the nuclear genome is a well-established mechanism of evolutionary change in eukaryotes. Such transfers have occurred throughout evolution, but so far, none has been shown unequivocally to occur de novo to cause a heritable human disease. We have characterized a patient with a de novo nucleic acid transfer from the mito-chondrial to the nuclear genome, a transfer that is responsible for a sporadic case of Pallister-Hall syndrome, a condition usually inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 29 publications
6
79
0
1
Order By: Relevance
“…Several TSIPs disrupted the coding region of a gene (Onozawa et al, 2015). Furthermore, a recent report described a constitutional 72-bp insertion of mitochondrial sequence into the coding region of GLI3 , leading to Pallister-Hall syndrome (Turner et al, 2003). Of note, the conception of this patient was temporally and geographically associated with high-level radioactive contamination following the Chernobyl accident (Turner et al, 2003).…”
Section: Potential To Cause Genetic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several TSIPs disrupted the coding region of a gene (Onozawa et al, 2015). Furthermore, a recent report described a constitutional 72-bp insertion of mitochondrial sequence into the coding region of GLI3 , leading to Pallister-Hall syndrome (Turner et al, 2003). Of note, the conception of this patient was temporally and geographically associated with high-level radioactive contamination following the Chernobyl accident (Turner et al, 2003).…”
Section: Potential To Cause Genetic Diseasementioning
confidence: 99%
“…Furthermore, a recent report described a constitutional 72-bp insertion of mitochondrial sequence into the coding region of GLI3 , leading to Pallister-Hall syndrome (Turner et al, 2003). Of note, the conception of this patient was temporally and geographically associated with high-level radioactive contamination following the Chernobyl accident (Turner et al, 2003). Although speculative, it is conceivable that a DNA DSB in the germ cell, caused by ionizing radiation, was repaired by a TSI derived from mitochondrial DNA in this individual.…”
Section: Potential To Cause Genetic Diseasementioning
confidence: 99%
“…The frequency of the insertion events and the site of integration are therefore critical factors influencing genomic stability. In humans these two aspects have been investigated for mobile elements, including long and short interspersed elements and retroviruses (Li et al 2001; Batzer and Deininger 2002), but much less is known about nuclear DNA sequences of mitochondrial origin (NUMTs), which have been found associated with diseases in humans (Willett-Brozick et al 2001; Borensztajn et al 2002; Turner et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…NUMTs usually present themselves in three forms: a) continuous stretches of DNA that align linearly with the original mtDNA sequence, b) scrambled sequences derived from different regions of the mitochondrial genome, and c) re-arranged pieces of mtDNA different mitochondria [55]. Starting with the discovery of NUMTs in yeast [25], scattered reports of mitochondrial fragments in human DNA surfaced [57, 74, 98, 113] until sequencing of the human genome showed hundreds of NUMTs. The first analyses by Mourier et al [66] and Tourmen et al [96] revealed between 280 and 296 NUMTs in the human genome, of which 94 were 1000 bp or longer.…”
Section: Numtogenesis In Evolutionmentioning
confidence: 99%